1987
DOI: 10.1177/019262338701500407
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes during Acute Acetaminophen-Induced Hepatotoxicity in the Mouse: A Time and Dose Study

Abstract: This study was undertaken to evaluate the early ultrastructural changes during the development of acetaminophen hepatotoxicity. Doses at or near the threshold for hepatotoxicity were selected to permit comparison of early reversible effects to those which ultimately progressed to necrosis in the absence of early agonal effects or drug-induced mortality. Both 300- and 600-mg/kg doses resulted in similar declines in hepatic glutathione levels to 14 and 22% of control values, respectively, by 2 hours, with more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 16 publications
5
50
0
1
Order By: Relevance
“…Mitochondrial dysfunction after toxic doses of APAP has been recognized in rodents since the 1980s, when inhibition of mitochondrial respiration and depletion of ATP were first described (15,16,44). More recent studies have shown the development of oxidative and nitrosative stress within mitochondria and occurrence of the mitochondrial MPT after APAP treatment (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial dysfunction after toxic doses of APAP has been recognized in rodents since the 1980s, when inhibition of mitochondrial respiration and depletion of ATP were first described (15,16,44). More recent studies have shown the development of oxidative and nitrosative stress within mitochondria and occurrence of the mitochondrial MPT after APAP treatment (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…The additional reactive metabolite depletes liver GSH and binds to proteins (11)(12)(13)(14). Ultrastructural and biochemical studies demonstrated that toxic doses of APAP could cause changes in the morphology and function of liver mitochondria (15,16). While it was clear from these data that mitochondrial injury occurs after treatment with large doses of APAP, it was not known how this developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested by Ruepp et al (2002) that the toxic cascade activates a number of genes involved in apoptosis, but energy-depletion and mitochondrial failure might divert the cell death program to necrosis. Similarly, Placke et al (1987) described that beside GSH-depletion oxidative stress also plays a central role in liver damage, since they observed ultrastructural changes in mitochondria early after application of high doses of APAP. Indeed, a recent quantitative analysis led Gujral et al (2002) to conclude that necrosis and not apoptosis was the principal mechanism of hepatocyte death after APAP-intoxication.…”
Section: Introductionmentioning
confidence: 92%
“…6,7) Therefore, studies on scavenging free radicals or reactive oxygen species (ROS) as well as reducing oxidative stress, and thereby avoiding hepatotoxicity, have received much attention in human health sciences. Biochemical studies suggested that toxic doses of APAP could cause changes in the morphology and function of liver mitochondria, 8,9) because of the binding of APAP more frequently to mitochondrial proteins, 10) which causes mitochondrial oxidative stress. 11) In the search for hepatoprotective agents from the natural sources, the closely relevant model system to human liver toxicosis could be an effective way to identify therapeutically applicable agents using most widely used drugs in the world, APAP.…”
mentioning
confidence: 99%